The green book : documenting black mobility in twentieth-century America - Toh, Eunice (2017)
The American road, long a symbol of freedom, has played a crucial role in shaping the identity of a nation founded on mobility. However, the promised freedom of an open road was not available to all—specifically black travelers. In 1877, Southern states, as a possible backlash to the Civil War and Reconstruction, imposed Jim Crow laws that formally relegated African Americans to the status of second-class citizens. For almost ninety years, a segregation system of “separate but equal” was enforced. While using public transportation for example, black passengers could only occupy “colored” seats at the rear of the bus, or in the Jim Crow car of the railroad. To avoid the demoralizing—and at times dangerous—experience of traveling by public transport, an increasing number of black travelers took to the highways for cross-country business trips and family vacations. However, the automobile could only offer so much security as racist sentiments were just as prevalent on the road.